2021
DOI: 10.1007/s10876-021-02131-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Fabrication of Gold Nanoparticles Embedded Dextran/ Silk Sericin Nanomaterials for the Treatment and Care of Wound Healing

Abstract: Gold-loaded nanoparticles are versatile nanomaterials that may be used in wound healing properties. The current study describes a wound dressing formulation focused on Gold-loaded Dextran/Silk Sericin nanoparticles. The Gold-loaded Dextran/Silk Sericin membranes were fabricated using Gold solutions inside the Dextran/Silk Sericin medium. The influence of various experimental conditions on Dextran/Silk Sericin nanoparticle formations were examined. The sizes of Dextran/Silk Sericin and Gold@Dextran/Silk Sericin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have revealed that natural SS act as reducing (the carboxylic acid group) and stabilizing agents for metal NPs and are environmentally friendly [ 74 , 90 ]. Silver (Ag), gold (Au), and zinc (Zn) nanoparticles have been widely used to prepare antibacterial SS composite materials [ 30 , 31 , 75 ]. The SS materials loaded with metal NPs effectively inhibit the skin-infecting bacteria, including E. coli , P. aeruginosa and S. aureus [ 30 , 32 , 66 , 68 , 91 ].…”
Section: Preparation and Antimicrobial Properties Of Ss Antimicrobial...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have revealed that natural SS act as reducing (the carboxylic acid group) and stabilizing agents for metal NPs and are environmentally friendly [ 74 , 90 ]. Silver (Ag), gold (Au), and zinc (Zn) nanoparticles have been widely used to prepare antibacterial SS composite materials [ 30 , 31 , 75 ]. The SS materials loaded with metal NPs effectively inhibit the skin-infecting bacteria, including E. coli , P. aeruginosa and S. aureus [ 30 , 32 , 66 , 68 , 91 ].…”
Section: Preparation and Antimicrobial Properties Of Ss Antimicrobial...mentioning
confidence: 99%
“…Anti-infection is a crucial task in the wound-healing process, especially for some chronic wounds. To enhance the antimicrobial properties of SS materials, different antimicrobial agents, including metal nanoparticles, natural antimicrobials, and antibiotics, have been incorporated into the composites, which have significantly promoted wound healing [ 30 , 34 , 37 , 64 , 66 , 75 , 81 , 82 ]. Moreover, some studies have demonstrated the anti-inflammatory effects of SS alone [ 142 ].…”
Section: Ss-based Composite Materials Promotes Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experimental results showed that wound healing was significantly accelerated and scar formation was significantly reduced. 138 Although AuNPs can inhibit bacterial growth and promote wound healing, more often AuNPs is used in combination with other antibacterial substances or particles. Li et al constructed a chitosan wound dressing embedded with Au-Ag nanoparticles, and compared with CS-Ag without Au, the antibacterial effect of CS-Au-Ag was significantly enhanced.…”
Section: Effects Of Nanoparticles On Wound Healingmentioning
confidence: 99%
“…However, gold nanoparticles (AuNPs) containing polycaprolactone nanofibers have a limited antibacterial action against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans (zone of inhibition values less than 3 mm) [12]. Furthermore, while AuNPs have the ability to limit bacterial growth and promote wound healing, they should be utilized in conjunction with other antibacterial chemicals or particles [13,14].…”
Section: Introductionmentioning
confidence: 99%